2012
DOI: 10.1016/j.stem.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in PTEN and mTORC2 Regulation of Hematopoietic Stem Cell Self-Renewal and Leukemia Suppression

Abstract: Pten deletion from adult mouse hematopoietic cells activates the PI3-kinase pathway, inducing hematopoietic stem cell (HSC) proliferation, HSC depletion, and leukemogenesis. Pten is also mutated in human leukemias, but rarely in early childhood leukemias. We hypothesized that this reflects developmental changes in PI3-kinase pathway regulation. Here we show that Rictor deletion prevents leukemogenesis and HSC depletion after Pten deletion in adult mice, implicating mTORC2 activation in these processes. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
205
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(220 citation statements)
references
References 50 publications
9
205
1
5
Order By: Relevance
“…Activation of mTorc2 by PI3K leads to mTor-catalyzed phosphorylation and activation of Akt on S473 (Akt-S473) 20 . Mutation of the mTorc2-specific component Rictor reverses the effects of Pten mutation in leukaemia 21 , demonstrating that the mTorc2/Akt-S473 pathway is an important downstream target of Pten (via PI3K) 4 . Consistent with Pten expression, Akt-S473 was absent in normal lung, AAH and adenomas (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of mTorc2 by PI3K leads to mTor-catalyzed phosphorylation and activation of Akt on S473 (Akt-S473) 20 . Mutation of the mTorc2-specific component Rictor reverses the effects of Pten mutation in leukaemia 21 , demonstrating that the mTorc2/Akt-S473 pathway is an important downstream target of Pten (via PI3K) 4 . Consistent with Pten expression, Akt-S473 was absent in normal lung, AAH and adenomas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pten mutation has little effect on hematopoietic stem cell differentiation before adulthood, but Pten becomes a critical tumour suppressor of leukaemia in adults 21 . Because of the linkage between ZEB1 and Pten we show here, it is of note that ZEB1 expression is closely linked to cell proliferation during development, and it is therefore downregulated in most postmitotic adult cells 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, deletion of Pten during hematopoiesis demonstrated that Pten is critical for suppressing the development of leukemia (7)(8)(9). Furthermore, studies using Raptor-or Rictordeficient mice revealed that activation of mTORC1 or -2 is required for the leukemogenesis evoked by Pten loss (10,11). However, the involvement of mTORC1 in leukemogenesis associated with other oncogenic signals, such as Ras, is not well understood.…”
mentioning
confidence: 99%
“…Altogether, this work suggested that Flk2 expression was associated with loss of self-renewal potential and initiation of robust proliferation in adult hematopoietic progenitors (10)(11)(12)14). During fetal hematopoiesis, however, activity of the FlkSwitch system correlated very differently with HSC phenotype and transplantability as compared to adult hematopoiesis, giving rise to the identification of the fetal drHSCs recently reported by Beaudin and coworkers (10 (16,17). Although transplantation assays have been instrumental to rigorously and prospectively define HSCs, findings by Beaudin and coworkers highlight the fact that transplantation into irradiated recipients remains an experimental assay, and that behavior of a given population of progenitors after transplantation (e.g., long-term reconstitution from drHSCs) does not necessarily match their in vivo activity (e.g., spontaneous disappearance of these cells in physiological conditions).…”
mentioning
confidence: 63%